Predominance of ST22-MRSA-IV clone and emergence of clones for methicillin-resistant staphylococcus aureus clinical isolates collected from a tertiary teaching hospital over a two-year period - Niek, Wen Kiong; Teh, Cindy Shuan Ju; Idris, Nuryana; Thong, Kwai Lin; Ponnampalavanar, Sasheela (Institute of Infectious Diseases, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most common nosocomial pathogens, causing mild to severe infections. This study aimed to determine the genotypic and phenotypic characteristics of clinical MRSA isolates collected from a teaching hospital from 2014 - 2015. These isolates were genotyped by multilocus sequence typing (MLST), staphylococcal cassette chromosomal mec (SCCmec) typing, virulence genes detection and pulsed-field gel electrophoresis (PFGE) and phenotyped based on their vancomycin susceptibility profiles. The most prevalent sequence type was ST22. ST3547 was identified from a blood isolate from 2015. Three SCCmec types (III in 26.26%, IV in 70.71% and V in 3.03%) were detected. Agr type I, II, III were detected among the isolates. The most prevalent virulence genes were hemolysin (100%) and intracellular adhesion (91.9%). At least one staphylococcal enterotoxins was detected in 83 (83.8%) of the isolates. All of the isolates were susceptible to vancomycin (MIC ≤ 2 µg/ml). Statistical analysis revealed significant increase in hypertension (p = 0.035), dyslipidemia and obesity (p = 0.046), and previous exposure to any quinolone (p = 0.010) cases over the two-year period. Emergence and circulation of community-associated MRSA variants were observed in our hospital. © 2019, National Institute of Health. All rights reserved.